Can Inorganic Bovine Bone Grafts Present Distinct Properties? - Desterro,Fernanda de Paula do (2014)
The aim of this study was to evaluate the physicochemical characteristics of 3 mineralized bovine inorganic biomaterials and correlate them with the dissolution rate. Bio-Oss(r), GenoxInorgânico(r), and Bonefill(r) were examined using field emission gun scanning electron microscopy (FEG-SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), specific surface area (BET), calcium/phosphorous molar ratio and a dissolution assay. Bio-Oss(r) showed a micro- and nanoporous structure consisting of 15-nm hydroxyapatite (HA) crystallites; Genox(r), a microporous structure composed of 39-nm HA crystallites; and Bonefill(r), micro- and nanoporous structure of indeterminable crystallite size. FTIR analysis showed that Bio-Oss(r) and Genox(r) were composed of calcium phosphate. The absorption bands of phosphate were poorly defined in Bonefill(r). By XRD, Bio-Oss(r) was shown to contain peaks related to the carbonated HA, whereas Genox(r) only contained peaks corresponding to HA. The broad bands in Bonefill(r) indicated low crystallinity. Bio-Oss(r) showed a greater surface area and calcium release rate than that of Genox(r). Although all biomaterials were of bovine origin, the different manufacturing processes result in materials with different physicochemical properties and may influence the biological and clinical response.